2005
DOI: 10.1038/nature03589
|View full text |Cite
|
Sign up to set email alerts
|

Notch signals control the fate of immature progenitor cells in the intestine

Abstract: The Notch signalling pathway plays a crucial role in specifying cellular fates in metazoan development by regulating communication between adjacent cells. Correlative studies suggested an involvement of Notch in intestinal development. Here, by modulating Notch activity in the mouse intestine, we directly implicate Notch signals in intestinal cell lineage specification. We also show that Notch activation is capable of amplifying the intestinal progenitor pool while inhibiting cell differentiation. We conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
674
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 818 publications
(716 citation statements)
references
References 31 publications
38
674
0
4
Order By: Relevance
“…23 Contrary to Drosophila, 38 Nle loss of function does not seem to interfere with the Notch pathway in the mouse hematopoietic 23 and intestinal (this study) lineages. Indeed, although increasing or decreasing Notch activity systematically results in strong variations of Hes1 expression levels in the intestinal crypt cells, [39][40][41][42][43] Hes1 mRNA levels were unchanged following Nle inactivation in the intestinal epithelium (Figure 3c and data not shown). Interestingly, premature differentiation toward the goblet cell lineage of intestinal stem/ progenitor cells is observed when Notch activity is inhibited.…”
Section: Discussionmentioning
confidence: 91%
“…23 Contrary to Drosophila, 38 Nle loss of function does not seem to interfere with the Notch pathway in the mouse hematopoietic 23 and intestinal (this study) lineages. Indeed, although increasing or decreasing Notch activity systematically results in strong variations of Hes1 expression levels in the intestinal crypt cells, [39][40][41][42][43] Hes1 mRNA levels were unchanged following Nle inactivation in the intestinal epithelium (Figure 3c and data not shown). Interestingly, premature differentiation toward the goblet cell lineage of intestinal stem/ progenitor cells is observed when Notch activity is inhibited.…”
Section: Discussionmentioning
confidence: 91%
“…Post-natal gut specific inactivation of RBP-J results in the complete loss of proliferating transient amplifying (TA) cells [124]. In a reciprocal experiment, expression of activated Notch1 (NICD) in the gut inhibits differentiation of crypt progenitors [125]. These genetic experiments establish Notch signaling as a gatekeeper for intestinal crypt cells in mice.…”
Section: Notch Signaling In Development and Differentiationmentioning
confidence: 97%
“…Notch signaling plays a key role specifying differentiation in the intestinal epithelium in developing and adult mice [18], [19], [20], [21]. Previously we have shown that conditional expression of an activated Notch mutant fused to Enhanced Green Fluorescent Protein (EGFP) (ICD-E) in the intestine of adult mice results in a transient increase in goblet cells on the villus, within 24 hours of Notch activation, followed by crypt apoptosis and shedding of the recombinant epithelium [20].…”
Section: Introductionmentioning
confidence: 99%